On the Tityus forcipula species group: redescription of Tityus forcipula (Scorpiones, Buthidae), description of a new Andean species, and notes on the taxonomy of the group - Moreno-González, Jairo A; Pinto-Da-Rocha, Ricardo; Cabra-García, Jimmy (Zootaxa, 2022)
The Tityus forcipula species group has had an intricate taxonomic history, changing its diagnostic characters and composition on several occasions. One of the alleged reasons for this taxonomic uncertainty is the use of superficial characters (i.e. raw similarity instead of putative synapomorphies) for species group delimitation. Here, we conducted a thorough phenotypic survey across the Tityus forcipula species group, as currently delimited, including characters that had been suggested elsewhere as putative synapomorphies for delimiting lineages within Tityus. In doing so we also redescribe Tityus forcipula and describe a new species belonging to the Tityus forcipula species group: Tityus moralensis sp. nov. based on specimens from the Andean region of Valle del Cauca department, Colombia. The Tityus forcipula species group is here delimited to Andean species from Colombia and Ecuador that share strongly sclerotized and brown colored pectines, basal middle lamellae of female pectines dilated and suboval or ovoid shaped, basal plate of female pectines without glandular region and telotarsi with two ventrosubmedian rows (type II) of stout macrosetae (i.e., Tityus crassicauda, Tityus cuellari, Tityus forcipula, Tityus fuhrmanni and Tityus moralensis sp. nov). The new Tityus species is placed into a phylogenetic context with other buthid species using DNA sequences (COI and 28S). Finally, we provide a map with updated distributional records of the Tityus forcipula species group.